Sex-related differences in clinical characteristics of children with ASD without ID: Results from the ELENA cohort - Dellapiazza, Florine; Michelon, Cécile; Rattaz, Cécile; Picot, Marie-Christine; Baghdadli, Amaria (Frontiers in Psychiatry, 2022)
Objective The literature on sex related-clinical differences for children with autism spectrum disorder (ASD) is highly contradictory, whereas this topic has major clinical implications. We aimed to investigate sex-related clinical differences in children with ASD without intellectual disability (ID). Materials and methods We compared 319 boys and 65 girls with ASD without ID, aged from 2 to 12 years, recruited from a multiregional cohort on their clinical profiles based on the scores for the Vineland-II, the SRS-2, the ADOS calibrated severity score, sensory processing, aberrant behaviors, and comorbidity rates. Results Our results confirm a high sex ratio of 4.9 males/females. Many similarities were found in the clinical profiles. However, we found that girls had higher SRS-2 total scores. In addition, there was a negative correlation between the SRS-2 total score and the intellectual quotient level (IQ) for girls only. Conclusion We confirm the higher rates of boys with ASD without ID. A comparison between the girls and boys showed them to have similar clinical profiles, except for the SRS- 2 total scores, which were higher among girls, suggesting more severe social impairment perceived by parents. Our findings that the cognitive level is related to ASD severity in girls should be taken into account during the diagnostic procedure in the clinical interpretation of gold-standard measures of ASD, and additional clinical observations are necessary. Clinical trial registration [ClinicalTrials.gov], identifier [NCT02625116s].